Validasi Model Hidrologi SWAT di Daerah Tangkapan Air Waduk Mrica - Lukman Hidayat; Putu Sudira; Sahid Susanto; Rachmad Jayadi (agriTECH, 2016)
Land cover index production has exceeded 80 % of the total area of  the upstream catchment area of Mrica reservoirs, indicating the occurrence of land conversion. Elementary hydrological model, is predicted as an extrapolation tool that can help to understand the complexity of watershed management, including land conversion. Soil Water Assessment Tool (SWAT) is a physically based, deterministic, continuous, watershed-scale hydrologic models that was developed by the USDA Agricultural Research Service. SWAT was developed from numerous individual models within a period more than 30 years, and has been applied in several areas. The aim of this study was applying the SWAT on the upstream region of Mrica reservoirs. The method of the research was using the SWAT modeling procedure through a systems based on input output processes (IO). Output model was in the form of flow rate, validated by means of calibration and verification using statistical and graphical criteria on monthly scale. The results showed that their value of R2 = 0.61, NSE = 0.61, PBIAS = -0.61 % and MB = -0.25 for calibration, and R2 = 0.74, NSE = 0.73, PBIAS = -4.06 % and MB = -1.57for verification. The value of the statistical test showed that the model SWAT has good degree of precision and accuracy in watershed modeling. NSE values > 0.65 indicates that the SWAT model has an accuracy of very good degree. Several challenges in this watershed modelling are the availability and adequacy of data, the optimizationof parameters, time and computer resources. ABSTRAKIndeks Penutupan Lahan (IPL) produksi yang telah melebihi 80 % dari total luas kawasan Hulu Daerah Tangkapan Air (DTA) waduk Mrica, mengindikasikan telah terjadinya alih fungsi lahan. Model hidrologi elementer, dipandang sebagai alat ekstrapolasi yang dapat membantu untuk memahami kompleksitas pengelolaan kawasan Daerah Aliran Sungai (DAS), di antaranya alih fungsi lahan. Soil Water Assessment Tool (SWAT) adalah model hidrologi skala DAS berbasis fisik, deterministik, dan kontinyu yang dikembangkan oleh USDA (United States of Department of Agriculture) Agricultural Research Service. Model SWAT dikembangkan dari sejumlah model-model individu dalam periode lebih dari 30 tahun, dan telah diaplikasikan pada beragam wilayah, dalam rentang waktu yang cukup lebar. Penelitian ini bertujuan untuk mengaplikasikan model SWAT pada kawasan hulu DTA waduk Mrica. Metode yang digunakan yaitu menjalankan prosedur pemodelan SWAT melalui pendekatan sistem yaitu proses Input Output (IO). Luaran model berupa debit aliran, yang kemudian divalidasi dengan cara kalibrasi dan verifikasi menggunakan kriteria statistik dan grafis pada skala bulanan. Hasilnya menunjukkan bahwa nilai R2 = 0,61, NSE = 0,61, PBIAS = -0,61 % dan MB = -0,25 untuk kalibrasi, dan R2 = 0,74, NSE = 0,73, PBIAS = -4,6 % dan MB = -1,57 untuk verifikasi. Nilai uji statistik tersebut menunjukkan bahwa model SWAT mempunyai tingkat presisi dan akurasi yang baik dalam pemodelan DAS. Nilai NSE > 0,65 mengindikasikan bahwa model SWAT yang diaplikasikan mempunyai tingkat akurasi mencapai derajat sangat baik. Tantangan yang dihadapi dalam pemodelan DAS ini yaitu ketersediaan dan kecukupan data, optimasi parameter, waktu dan sumberdaya komputer.